Can NOx reduction by CO react over carbon‐based single‐atom catalysts at low temperatures? A theoretical study. Issue 1 (12th September 2021) - Shi, Jie; Zhang, Wei; Li, Hui; Pu, Yuan; Wang, Dan; Chen, Jian‐Feng
Abstract: First principles studies combined with the microkinetic analysis were performed to study the reliability and reaction mechanisms of single‐atom‐doped graphene materials in catalyzing NOx reduction with CO. By screening the 3d transition metals (Sc‐Zn) and group IV elements (Si and Ge), it was found that the Ti‐ and Co‐doped graphene sheets (TiGr and CoGr), respectively, exhibited excellent catalytic activities in the NO/NO2 ‐to‐N2 O and the N2 O‐to‐N2 processes at a relatively low temperature (450 K). Therefore, the tandem catalyst (TiGr + CoGr) can be a promising catalyst in NOx reduction with CO. It was further revealed that the combination of adsorption energy and electronegativity was a good descriptor to predict the activation energies. The obtained results provide useful information for rational design of carbon‐based single‐atom catalysts for NOx reduction by CO at low temperatures.